Mucosal associated invariant T cells and related CD161 expressing T lymphocytes - Fergusson, J; Joannah Fergusson (2015)
The C-type lectin CD161 is expressed by a large number of T lymphocytes, with approximately a quarter of both T cell receptor (TCR)αβ+ and TCRγδ+ T cells expressing this marker. Within CD8+ T cells, a large proportion of these are comprised of Mucosal Associated Invariant T (MAIT) cells, a novel innate-like lymphocyte subset characterised by expression of a semi-invariant TCR together with high levels of CD161 (CD161++). These cells display a phenotype reflective of type 17 CD4+ helper T cells (Th17), which are also hallmarked by CD161 expression. Both MAIT and Th17 cells arise from preprogrammed progenitors, identifiable within umbilical cord blood by expression of CD161. Thus, CD161 appears to identify cells of a pre-determined and distinct phenotype. Whether this reflects a common transcriptional programme, developmentally induced within these cells, and further whether this extends to other CD161 positive T cells, was examined here by mRNA microarray analysis. This analysis identified a shared transcriptional signature and common innate-like function of all CD161 expressing T lymphocytes, and independent of TCR expression or lineage. Furthermore, a population of CD8+ T lymphocytes expressing lower levels of CD161 which overlap phenotypically with CD161++CD8+ MAIT cells was identified by both mRNA microarray analysis and mass cytometry (CyTOF); the CD161+CD8+ T cell population. TCR repertoire analysis, flow cytometry and cell culture experiments were utilised to investigate the origin of this subset, and its phenotype and function in both health and disease investigated in depth. This revealed a pre-programmed, tissue-resident memory population with potent effector functions. Both CD161++ MAIT and CD161+CD8+ T cells expressed high levels of the drug efflux pump MDR1, previously described to confer drug resistance to certain malignant cells. The significance of expression of this pump was hence investigated to determine its potential affect on the success of a variety of clinical therapies.